A Critical Analysis of Measurement Models of Export Performance - Jorge Carneiro (BAR: Brazilian Administration Review, 2007)
Poor conceptualization of the export performance construct may undermine theory development efforts and may be one of the reasons behind the often conflicting findings in empirical research on the export performance phenomenon. This article reviews the conceptual and empirical literature and proposes a new analytical scheme that may serve as a standard for judging content validity and a guiding yardstick for drawing operational representations of the construct. A critical assessment of some of the most frequently cited measurement frameworks, followed by an analysis of recent (1999-2004) empirical research, leaves no doubt that there are flaws in the conceptualization and operationalization of the performance construct that ought to be addressed. A new measurement model is advanced along with some guidelines which are suggested for its future empirical validation. The new measurement framework allegedly improves on other past efforts in terms of breadth of coverage of the construct’s domain (content validity). It also offers a measurement perspective (with the simultaneous use of both formative and reflective approaches) that appears to reflect better the nature of the construct.